Evaluating an Art Therapy Program in an Outpatient Psychiatric Hospital Setting for Individuals With Mood Disorders - Bromwich, Laura; Slyepchenko, Anastasiya; Berry, Sharon; Simons, Sharon; Davey, Caitlin (Canadian Journal of Counselling and Psychotherapy, 2024)
The aim of this program evaluation was to assess the impact of an 8-week art therapy intervention for adults in a hospital-based outpatient mood disorders clinic on depressive symptoms and overall quality of life and to examine how these symptoms may change over time by primary psychiatric diagnosis. Following a convergent mixed-methods approach, data collection included quantitative and qualitative patient feedback regarding program implementation to improve delivery. Pre- and post-treatment results from this evaluation are presented (n = 88), including patient feedback on the program (n = 34). Independent of primary diagnosis, patients experienced improvements in depressive symptoms (p < .001, ηp2 = .33), anxiety symptoms (p < .001, ηp2 = .16), and stress symptoms (p < 0.01, ηp2 = 15), as measured by the Depression Anxiety Stress Scales-21. In addition, patients experienced improvement in scores on the Quality of Life Enjoyment and Satisfaction Questionnaire—Short Form (p < .001, ηp2 = .37). Findings suggest that structured group art therapy can reduce symptoms of depression, anxiety, and stress and can improve quality of life in a Canadian outpatient psychiatric setting. Participants were generally satisfied with the quality of this service delivery and provided constructive qualitative feedback to help improve the service.